2015
DOI: 10.1111/head.12547
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Migraine Is Associated With Reduced Corneal Nerve Fiber Density and Symptoms of Dry Eye

Abstract: Background We used in vivo corneal confocal microscopy to investigate structural differences in the sub-basal corneal nerve plexus in chronic migraine patients and a normal population. We used a validated questionnaire and tests of lacrimal function to determine the prevalence of dry eye in the same group of chronic migraine patients. Activation of the trigeminal system is involved in migraine. Corneal nociceptive sensation is mediated by trigeminal axons that synapse in the gasserian ganglion and the brainste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 17 publications
9
52
0
1
Order By: Relevance
“…Since ophthalmologists often come across with eye related migraine complaints such as periorbital pain or visual auras, they have long been studying the mechanisms of this mysterious disease [26]. As a result, there are several studies available in the ophthalmic literature revealing relationship between migraine and dry eye, glaucoma, optic nerve/visual field changes and peripapillary retinal thinning [27][28][29][30]. As the vasogenic theory [31] is one of the two competing theories dominating the discussion of migraine pathogenesis, the choroid-being the highly vascular structure of the eye-has become the center of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Since ophthalmologists often come across with eye related migraine complaints such as periorbital pain or visual auras, they have long been studying the mechanisms of this mysterious disease [26]. As a result, there are several studies available in the ophthalmic literature revealing relationship between migraine and dry eye, glaucoma, optic nerve/visual field changes and peripapillary retinal thinning [27][28][29][30]. As the vasogenic theory [31] is one of the two competing theories dominating the discussion of migraine pathogenesis, the choroid-being the highly vascular structure of the eye-has become the center of interest.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo confocal microscopy showed significantly decreased corneal nerve fiber density in migraine patients, and all the patients with migraine had dry eye symptoms 78. A large population-based study in Korea also revealed that patients with migraine had significantly higher risk of DED 79…”
Section: Association With Neurological Problemsmentioning
confidence: 96%
“…Association between chronic migraine and DED was also suggested 78. In vivo confocal microscopy showed significantly decreased corneal nerve fiber density in migraine patients, and all the patients with migraine had dry eye symptoms 78.…”
Section: Association With Neurological Problemsmentioning
confidence: 99%
“…Плотность нервных волокон рассчитывалась следующим образом: длина нерв-ных волокон  коэффициент (0,00075)/площадь сканирования. Коэффициент извитости рассчи-тывался автоматически [22].…”
Section: таблицаunclassified